Campylobacter fetus: revisão sistemática, desenvolvimento e caracterização antigênica da proteína SapA mutante com potencial imunobiólogico - Balzan, Cláudia (2019)
Bovine genital campylobacteriosis (BGC) is an important reproductive disease of the venereal nature, caused by the bacterium Campylobacter fetus subsp. venerealis and entails worldwide economic losses. The main virulence factors of this agent are related to adhesion, motility, surface proteins, production of toxins and secretion and regulation systems. This pathogen has surface proteins (SapA), which are considered important in the pathogenesis of CGB due to antigenic variation and are responsible for the persistence of infection in the bovine genital tract. Sampling and diagnosis are laborious, and the recommended samples for diagnosis are muco vaginal, preputial smegma and semen, placenta and aborted fetuses. The prevention and control of this disease are based on vaccination, the use of bulls negative for the disease and the implementation of artificial insemination programs. In order to simplify the laboratory procedures, this study aimed to standardize the production of a chimeric protein of C. fetus and evaluate its potential as a tool for the diagnosis and prevention of BGC. Using nine sapA sequences of C. fetus gene publicly available, two regions were determined for the construction of a synthetic gene, called sapAN78, with the possibility of cloning and expression of the whole gene and also of the two subunits. The whole fragment and subunits were cloned into plasmid pAE, expressed by Escherichia coli BL21 (DE3) pLySs and purified by nickel affinity chromatography. Recombinant chimera of approximately 60 kDa and subunits were obtained in significant amounts as inclusion bodies, solubilized with urea and detected by Western blot with anti-polyhistidine monoclonal antibody and by antibodies present in BGC positive bovine serum. rSapAn78 was used for rabbit hyperimmunization, presenting seroconversion from the first immunization and the antibodies produced at the end of the hyperimmunization protocol were avid by the ammonium thiocyanate assay. These antibodies also recognized the rSapAn78 in Dot blot as well as rSapAn78 and native proteins in C. fetus strains by Western blot and ELISA. In this way, the immunogenicity and antigenicity of the constructed chimeric protein and its potential for applications in future research for the diagnosis and prevention of BGC were demonstrated.